2020
DOI: 10.3389/fpsyt.2020.00668
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-Related Quality of Life and Influencing Factors for COVID-19 Patients, a Follow-Up at One Month

Abstract: Objective: To survey the health-related quality of life (HRQoL) and its influencing factors among patients with COVID-19 in their first medical follow up. Methods: All patients diagnosed with COVID-19 were discharged from 12 hospitals in Wenzhou, Zhejiang from Jan 17, 2020 to Mar 20, 2020. Prospectively collected and analyzed data included demographics, clinical symptoms, comorbidity, and chest CT imaging features at the first follow up, 1 month after discharge. All patients underwent the HRQoL evaluation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
229
8
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(273 citation statements)
references
References 30 publications
29
229
8
7
Order By: Relevance
“…Among the discharged COVID-19 patients, the health-related quality of life was poor, and patients suffered from significant physical and psychological impairment. [ 7 ] Therefore, it is urgent to perform safe and effective rehabilitation interventions for discharged COVID19 patients. The present study demonstrated that Liuzijue exercises improved the respiratory function and exercise capacity of patients previously infected with the SARS-CoV-2 coronavirus at 4-weeks follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the discharged COVID-19 patients, the health-related quality of life was poor, and patients suffered from significant physical and psychological impairment. [ 7 ] Therefore, it is urgent to perform safe and effective rehabilitation interventions for discharged COVID19 patients. The present study demonstrated that Liuzijue exercises improved the respiratory function and exercise capacity of patients previously infected with the SARS-CoV-2 coronavirus at 4-weeks follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Among discharged COVID-19 patients, the health-related quality of life is poor, and patients suffer from significant physical and psychological impairment. [ 7 ] Therefore, it is extremely urgent to perform safe and effective rehabilitation intervention for discharged COVID19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of COVID-19 has influenced every aspect of life globally [ 7 , 8 ], especially the healthcare system. To the best of our knowledge, this is the first study that changes in the neurology department in tertiary public hospital centers during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with SARS COV-2, the psychological and physical burden result in loss of perceived QOL (Chen et al, 2020). But the perceived QOL of health professional is still undocumented.…”
Section: Quality Of Life Of Health Care Professionals In Pandemic Timesmentioning
confidence: 99%